A savings intervention to reduce men’s engagement in HIV risk behaviors: study protocol for a randomized controlled trial - Teniola I. Egbe; Ouma Dan Omollo; Julius Oduor Wesonga; Elizabeth F. Bair; Averi Chakrabarti; Mary E. Putt; Connie L. Celum; Carol S. Camlin; Sue Napierala; Kawango Agot; Harsha Thirumurthy (Trials, 2022)
Abstract Background In much of eastern and southern Africa, the incidence of HIV and other sexually transmitted infections (STIs) remains high despite the scale-up of promising biomedical and behavioral interventions. Studies have documented the crucial role of transactional sex—the exchange of money, material support, or goods, in sexual relationships—and heavy alcohol use in contributing to men’s and women’s health outcomes. Existing policy responses to this challenge have largely focused on women, through the provision of pre-exposure prophylaxis (PrEP) or structural interventions such as education subsidies and cash transfers. However, the effectiveness of these interventions has been hindered by the relative lack of interventions and programs targeting men’s behavior. We describe the protocol for a study that will test an economic intervention designed to reduce men’s engagement in HIV/STI-related risk behaviors in Kenya. Methods We will conduct a randomized controlled trial among income-earning men in Kenya who are aged 18–39 years and self-report alcohol use and engagement in transactional sex. The study will enroll 1500 participants and randomize them to a control group or savings group. The savings group will receive access to a savings account that includes lottery-based incentives to save money regularly, opportunities to develop savings goals/strategies, and text message reminders about their savings goals. The control group will receive basic health education. Over a period of 24 months, we will collect qualitative and quantitative data from participants and a subset of their female partners. Participants will also be tested for HIV and other STIs at baseline, 12, and 24 months. Discussion The findings from this study have the potential to address a missing element of HIV/STI prevention efforts in sub-Saharan Africa by promoting upstream and forward-looking behavior and reducing the risk of acquiring HIV/STIs in a high HIV/STI burden setting. If this study is effective, it is an innovative approach that could be scaled up and could have great potential for scientific and public health impact in Kenya. Trial registration ClinicalTrials.gov NCT05385484 . Registered on May 23, 2022